ANALISIS VALUASI NILAI WAJAR SAHAM PT. ADARO ENERGY TBK MENGGUNAKAN METODE FREE-CASH FLOW TO FIRM (FCFF) - Ecryna Cyntia Hutapea; Tyara Pratiwi Poernomoputri; Pardomuan Sihombing (Bina Nusantara University, 2013)
PT Adaro Energy Tbk, an Indonesian private company engaged in coal mines and became the largest thermal coal producers both in Indonesia, which also operates coal mines and have the single biggest in the southern hemisphere. Coal products PT Adaro Energy Tbk has medium levels of energy content, and assign its trademark with the name of the Envirocoal. PT Adaro Energy Tbk is officially listed on the Indonesia Stock Exchange (BEI) on July 16, 2008 and was recorded as the largest company in the history of the Stock Exchange for deals done in rupiah (whereas in the US is the currency of the latter), and an IPO 4th largest for the year 2008 in Asia (excluding Japan) with a stock offering as much 11.139331 billion shares. To assess the stock price of PT Adaro Energy Tbk in the market, the valuation of shares is needed, where the valuation of these shares will be known intrinsic value (fair price). The method used in this valuation is the Discounted Cash Flow method using the model of Free Cash Flow to Firm. Valuation results would be very useful to be used as the basis for making investment decisions to buy, hold or sell stock. Based on the calculation that stock valuations have been carried out, obtained the intrinsic value of PT Adaro Energy Tbk amounting to Rp 1,570 while the price of shares in PT Adaro Energy Tbk as at July 6, 2012 is 1,866, with the conclusion of the stock price of PT Adaro Energy Tbk undervalued or is below the market price.